Sclerostin as a novel marker of bone turnover in athletes - Zagrodna, A; Jóźków, P; Mędraś, M; Majda, M; Słowińska-Lisowska, M (Biology of Sport, 2016)
Sclerostin is a protein secreted by osteocytes that acts as an inhibitor of bone formation. It has been shown that physical activity affects sclerostin concentration and thus bone remodelling. The aim of the study was to evaluate serum concentrations of sclerostin, selected bone turnover markers (PTH, P1NP), 25(OH) D3 and the intake of calcium and vitamin D in physically active versus sedentary men. A total of 59 healthy men aged 17-37 were enrolled in the study (43 athletes and 16 non-athletes). The mean sclerostin concentration in the group of athletes (A) was significantly higher than in non-athletes (NA) (35.3±8.9 vs 28.0±5.6 pmol• l-1, p= 0.004). A compared with NA had higher concentrations of P1NP (145.6±77.5 vs 61.2±22.3 ng• ml-1, p= <0.0001) and 25(OH)D3 (16.9±8.4 vs 10.3±4.3 ng • ml-1, p= 0.004) and lower concentrations of PTH (25.8±8.3 vs 38.2±11.5 pg• ml-1, p= <0.0001). Vitamin D deficiency was found in 77% of A and 100% of NA. A and NA had similar daily energy intake. They did not differ as to the intake of calcium and vitamin D. We observed a negative correlation between the serum concentrations of sclerostin and calcium in the studied subjects. Our results suggest that regular, long-lasting physical training may be associated with higher concentration of sclerostin. It seems that increased sclerostin is not related to other bone turnover markers (PTH, P1NP).